Love and Death in Egypt and Rome - Targoff, Ramie (Memoria di Shakespeare. A Journal of Shakespearean Studies, 2018)
This paper looks at Shakespeare’s use of Italian sources in writing Romeo and Juliet. My emphasis will be on the ways in which Shakespeare understood Italian ideas about death and burial to differ from those prevalent in England, and to explore what he gained by refuting the central premise of all of Romeo and Juliet’s Italian sources: that their love would have an afterlife beyond the grave. The paper will also consider Shakespeare’s return to the topic in Antony and Cleopatra, in which he imagines an alternative model for conceiving of posthumous love. Keywords: Romeo and Juliet, Antony and Cleopatra, Death, Burial, Posthumous love